Vedinių su priesaga *-mo- raida - Ambrazas, Saulius (Baltistica, 2007)
DEVELOPMENT OF DERIVATIVES WITH THE SUFFIX *-mo-Adjectives with the suffix *-mo- have been formed from substantives (cf. Lith. tólimas / tólymas and Latv. dial. tuôl’eims ‘distant’; Pruss. *auktimas ‘high’; Skr. agrimá- ‘the first, who is at the head’) and verbs (cf. Lith. dial. ãpsukmas ‘sewn round’, pliùkšmas ‘deflated, limp’; OLith. laimas ‘happy’ and Pruss. etnīstislaims (gnadenreich) III 631; Lith. liñksmas and Latv. lìksms ‘merry, gay, joyfull’, Gmc. *werma- ‘warm’, Skr. bhīmá- ‘terrible, frightfull’, Toch. A, B cämpamo- ‘well-to-do, rich’, Hitt. kišamma- ‘combed’) from the Late Proto-Indo-European. The gratest part of them became participles in the Baltic, Slavic and Albanian languages.On the other hand, the use of derivatives with the suffix *-mo- in the position of abstract nouns is also very old, cf. semanticaly concretized and derivationaly indissoluble abstract noun, in herited from Proto-Indo-European, Lith. dmas (dmai), Latv. dũmi, Pruss. dumis (rauch) E 39, Slav. *dymъ, Latv. fūmus, Skr. dhūmó- ‘smoke’ and Gk. θῡ‑μός with abstract meaning ‘soal, vitality, passion,    need’ : dhe-/dh-/dhū- ‘blow; breathe; choke; smoke; rush; disperse; whirl, move, stir’.In the East Baltic languages abstract nouns with the derived suffixes, based on *-mo-, became productive, cf. nomina actionis with *-i-mo- in Lithuanian (cf. gyvẽnimas ‘life’) and corresponding derivatives with *-u-mo- in Latvian (cf. ìeradums ‘custom, habit’).
Keywords: priesaga *-mo-